Mechanical Stretch Induces Smooth Muscle Cell Dysfunction by Regulating ACE2 via P38/ATF3 and Post-transcriptional Regulation by miR-421 - Liu, Xiaolin; Liu, Xinxin; Li, Mengmeng; Zhang, Yu; Chen, Weijia; Zhang, Meng; Zhang, Cheng; Zhang, Mei (Frontiers in Physiology, 2021)
Mechanical stretch promotes deregulation of vascular smooth muscle cells (VSMCs) functions during hypertension-induced vascular remodeling. ACE2 has a wide range of cardiovascular and renal protective effects. Loss of ACE2 is associated with cardiovascular disease, but little is known about the regulation of its expression, especially by abnormal mechanical stretch during hypertension. The present study was designed to investigate the contribution of ACE2 to vascular remodeling under mechanical stretch and to assess the possible underlying mechanisms. The abdominal aortic constriction model was established to mimic the environment in vivo. FX-5000T Strain Unit provided mechanical stretch in vitro. Gain-of-function was used to analyze the role of ACE2 played in the proliferation, migration, apoptosis and collagen metabolism of the VSMCs. RT-qPCR, Western blot, luciferase assay and ChIP assay were used to elucidate the molecular mechanism of ACE2 expression regulated by stretch. We found that mechanical stretch modulated the expression of the ACE2/Ang-(1-7) and ACE/AngⅡ axis. ACE2 was mechanically sensitive and was involved in stretch-induced dysfunction of VSMCs. The p38 MAPK/ATF3 pathway and miR-421 participated in the regulation of ACE2. Thus, ACE2 may contribute to the development of vascular remodeling under conditions of mechanical stretch.